(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2018)
In the case of a radiological accident there are characteristic phases: discovery and initial assistance with first aid; the triage and monitoring of the affected population; the release of the affected people; forward the victims to medical care; as well as the preparation of the report on the accident. In addition, studies and associated researches performed in the later period. Monitors, dosimeters and measurement systems should be calibrated by contaminating radionuclide standards. The radioactive sources used must be metrological reliable. In Brazil, this function is performed by LNMRI/IRD/CNEN, designated by INMETRO, which Radionuclide Metrology Laboratory is responsible for the standardization and supplying of radioactive sources in different geometries and matrices. This laboratory has a stock of radionuclide solutions with controlled environmental variables for the preparation of sources, which are calibrated and standardized by mean of primary and secondary methods. It is also responsible for the dissemination of standards and, in order to establish the metrological traceability of national standards, participates in international key-comparisons promoted by BIPM and regional metrology organizations. Internally, it promotes the National Comparison Programs for laboratories that analyze environmental samples and the traceability for radiopharmaceuticals producing centers and nuclear medicine services in the country. The paper presents the demand for 137Cs related to the radioactive accident in Goiania/Brazil and the significant results for the main radionuclides standardized by the Radionuclide Metrology Laboratory by international key-comparisons and national comparisons to provide metrological traceability. With the obtained results, the LNMRI integrates the international metrology BIPM network and fulfills its function of supplying, with about a hundred of radioactive standards, the country’s needs in different applications, including attendance to radiological accident.